Co-creating visual representations of safe spaces with mental health service users using photovoice and zoom. (December 2021) - Dare, Julie; Seiver, Helen; Andrew, Lesley; Coall, David A; Karthigesu, Shantha; Sim, Moira; Boxall, Kathy
Abstract: This paper examines methodological issues related to an innovative online qualitative research project that explored 'safe spaces' with mental health service users. The project used photovoice and focus groups conducted via Zoom videoconferencing software. Eleven participants shared photographs, discussing their meaning and significance in relation to 'safe spaces'. The photographs were then synthesised into an artist's impression of a safe space and transcripts of the online photovoice discussion analysed thematically and triangulated with the artist's impression. The paper provides a reflexive discussion of the research process and explores methodological and ethical implications of conducting sensitive qualitative research in online spaces. Highlights: Videoconferencing can create a safe space for researching mental health issues. Innovative digital research reduces barriers for mental health service users. Researcher subjectivity in photovoice reduces researcher/participant hierarchy. Ground rules, extra confidentiality measures promote safe online research spaces. Online photovoice enables a safe platform for participants viewed as vulnerable.